The sieve-element endoplasmic reticulum: A focal point of phytoplasma-host plant interaction? - Musetti, Rita; Pagliari, Laura; Mian, Giovanni; De Oliveira Cantao, Fernando R.; Bernardini, Chiara; Santi, Simonetta; van Bel, Aart J. E. (Frontiers in Microbiology, 2023)
The rough endoplasmic reticulum (r-ER) is of paramount importance for adaptive responses to biotic stresses by reason of an increased demand for de novo synthesis of immunity-related proteins and signaling components. In nucleate cells, disturbance of r-ER integrity and functionality leads to the “unfolded protein response” (UPR), which is an important component of innate plant immune signalling. In contrast to an abundance of reports on r-ER responses to biotic challenges, SE-ER (sieve-element endoplasmic reticulum) responses to phytoplasma infection have not been investigated. We found that morphological SE-ER changes, associated with phytoplasma infection, are accompanied by differential expression of genes encoding proteins involved in shaping and anchoring the reticulum. Phytoplasma infection also triggers an increased release of bZIP signals from the (SE-ER)/r-ER and consequent differential expression of UPR-related genes. The modified expression patterns seem to reflect a balance act between survival of host cells, needed for the phytoplasmic biotrophic lifestyle, and phytoplasmas. Specialized plasmodesmata between sieve element and companion cell may provide a corridor for transfer of phytoplasma effectors that induce UPR-related gene expression in companion cells.